Analysis of Longitudinal Cracks in Multilayered Beams with Account of the Material Nonlinearity - Rizov, V.I. (Проблемы прочности, 2017)
The present paper reports a theoretical study of longitudinal fracture in multilayered beams with taking into account the material non-linearity. The study was performed in terms of the strain energy release rate by using the classical beam theory. The analysis developed holds for cracked beams whose layers may have different thickness. Besides, the mechanical behaviour of each layer may be described by different non-linear stress-strain relations. Also, the crack may be located arbitrary along the beam height. The strain energy release rate was expressed in a function of the bending moments and axial loads in the cross-sections ahead and behind the crack front. In this way, non-linear fracture analyses of multilayered beams can be carried-out in a closed analytical form. It was shown that the analysis developed is a useful tool for the understanding of non-linear longitudinal fracture in multilayered beam configurations. В рамках классической теории балок на основании критерия скорости высвобождения энергии деформации выполнен аналитический расчет прочности многослойных балок с продольной трещиной с учетом неупругости материала. Полученные расчетные соотношения применимы к многослойным балкам со слоями различной толщины, напряженно-деформированное состояние каждого из которых может описываться индивидуальным нелинейным уравнением напряжение–деформация. Для продольной трещины с произвольным расположением по высоте балки определяется скорость высвобождения энергии деформации как функция изгибающих моментов и осевых нагрузок, действующих в сечениях балки, расположенных впереди и позади фронта трещины. Таким образом можно определить условия разрушения многослойных балок в замкнутом виде. Предложенный подход позволяет выявить особенности неупругого деформирования и разрушения многослойных балок с трещиной. У рамках класичної теорії балок на основі критерію швидкості звільнення енергії деформації виконано аналітичний розрахунок міцності багатошарових балок із поздовжньою тріщиною з урахуванням непружності матеріалу. Отримані розрахункові співвідношення можна використати до багатошарових балок із шарами різної товщини, напружено-деформований стан кожного з них може описуватися індивідуальним нелінійним рівнянням напруга–деформація. Для поздовжньої тріщини з довільним розташуванням по висоті балки визначається швидкість звільнення енергії деформації як функція згинальних моментів і осьових навантажень, що діють у перетинах балки, розташованих попереду і позаду фронту тріщини. Таким чином можна визначити умови руйнування багатошарових балок у замкнутому вигляді. Запропонований підхід дозволяє виявити особливості непружного деформування і руйнування багатошарових балок із тріщиною.